Results of the TeachWell worksite wellness program. - Resnicow, K (1998)
OBJECTIVE: This study examined whether providing a school-based teacher wellness program enhances the impact of a health curriculum on student outcomes and improves cognitive, behavioral, and physiological outcomes among participating teachers. METHODS: Thirty-two elementary schools were randomly assigned to experimental or comparison conditions. Comparison group schools received the Gimme-5 program, a curriculum designed to increase fourth and fifty graders' consumption of fruits and vegetables. Experimental schools received Gimme-5 and the teacher wellness program, which included 54 workshops over 2 years, along with several schoolwide health activities. Physiological, behavioral, and cognitive outcomes were assessed in teachers and students. RESULTS: There was no evidence that the intervention favorably modified any student or teacher end points; nor did intervention teachers deliver the Gimme-5 program with greater fidelity than comparison teachers. CONCLUSION: Confidence in the null results is bolstered by the randomized design, baseline sample equivalence, appropriate mixed-model analyses, and lack of selective or differential attrition. Insufficient participation in the wellness program appears a likely explanation for the lack of teacher and student effects. Factors specific to the school setting and intervention may have diminished participation and, thus, intervention effects.